Use of the suzuki cross-coupling reaction to synthesize 5-(methoxymethoxy)-2-methylidenepentanol - Hoan, Duong Quoc (Vietnam Journal of Chemistry, 2015)
Synthesis of silanediol inhibitor 1 for human heart chymase (HHC) depends on synthesis of 5-(methoxymethoxy)-2-methylidenepentanol (2). A four step sequence was successful using the Csp3-Csp2 Suzuki cross coupling reaction between 2-[3-(methoxymethoxy)propyl]-4,4,5,5-tetramethyl-1,3,2-dioxaborolane (8) and 2-iodoprop-2-en-1-ol (9) to produce the allyl ancohol 2 in 38 % yield. The PdCl2(dppf) (5 mol%), TlOH (5 equiv) in THF/water at 50 °C was found to be the best condition for this reaction.